PENGARUH KINERJA KEUANGAN TERHADAP KEBIJAKAN PEMBAGIAN DIVIDEN PADA PERUSAHAAN CONSUMER GOODS - Hidayati, Fitri; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The examination is conducted to find out whether debt to equity ratio, return on equity, and price toearnings ratio have influence to the dividend payout ratio (DPR).The multiple linear regressions areused as the analysis technique. The hypothesis is tested by using t-test in order to find out theinfluence of each variable. The F test is conducted to test the model suitability which has been used.The examination has been conducted by using SPSS 20. The result of the t-test shows that debt toequity ratio (DER) does not have any influence with negative direction whereas return on equity andprice to earnings ratio have influence with positive direction. The F test shows that the model whichhas been used in the research is suitable (fit). It can be concluded that in t-test only ROE and PER hasinfluence to the dividend payout ratio whereas the financial performance which is used in model hasinfluence to the dividend payout ratio.Keywords: debt to equity ratio (DER), return on equity (ROE), price to earnings ratio (PER),dividend payout ratio.